2020
DOI: 10.1002/adsc.202001416
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 2‐Cyano‐2‐(2‐nitrobenzenesulfonyloxyimino) Acetate (ortho‐NosylOXY)‐Mediated Double Beckmann Rearrangement of Ketoximes under Microwave Irradiation: A Mechanistic Perception

Abstract: A method for Beckmann rearrangement using ethyl 2‐cyano‐2‐(2‐nitrobenzenesulfonyloxyimino) acetate (o‐NosylOXY) under microwave irradiation is reported. Ketoximes (19 examples) are converted to the corresponding amides/lactams with 69–97% yields in ∼10 minutes without any Lewis acid or co‐catalyst. This is an example of halogen‐free organocatalytic Beckmann rearrangement. Nuclear magnetic resonance (NMR)‐ and high‐resolution mass spectrometry (HRMS)‐based detailed mechanistic investigation suggest that o‐Nosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Various catalysts have been devised in recent years to facilitate the heterolysis of nitrogen–oxygen bond in order to achieve this transformation, but there are still certain drawbacks. Such as o -NosylOXY, 20 required microwave irradiation and high temperature. In 2020, Xu reported that HCl·DMPU assisted conversion of aldehydes into nitriles while HCl–DMPU is a solution emitting fumes.…”
mentioning
confidence: 99%
“…Various catalysts have been devised in recent years to facilitate the heterolysis of nitrogen–oxygen bond in order to achieve this transformation, but there are still certain drawbacks. Such as o -NosylOXY, 20 required microwave irradiation and high temperature. In 2020, Xu reported that HCl·DMPU assisted conversion of aldehydes into nitriles while HCl–DMPU is a solution emitting fumes.…”
mentioning
confidence: 99%
“…On the other hand, Ethyl‐2‐cyano‐2‐(2‐nitrophenylsulfonyloximino)acetate ( ortho ‐ NosylOXY, I , Scheme 1) is a versatile coupling reagent that can be used for the synthesis of amides and peptides in both solid and solution phases, [24a] amide and nitrile from ketoxime and aldoxime respectively, [24b–c] acetal/thioacetal from aldehydes, [24d] benzoxazole, benzothiazole, [24e] and alcohols [24f] from a carboxylic acid. Besides these, we have previously reported Lossen's rearrangement by two similar reagents [25] .…”
Section: Methodsmentioning
confidence: 99%
“…[227] Nonetheless, Mandal and his colleagues achieved an organocatalyzed Beckmann rearrangement without the involvement of inorganic materials. [228] They employed o-NosylOXY (depicted in Figure 51a) under microwave irradiation and straightforward reaction conditions. This method exhibited a broad substrate scope and yielded minimal waste except during purification.…”
Section: Rearrangementsmentioning
confidence: 99%